International treaties (Mu'ahadat) in Islam theory and practice in the light of Islamic international law (Siyar) according to orthodox schools - Bsoul, Labeeb Ahmed (University Press Of America, 2008)
International Treaties (Mu'ahadat) in Islam: Theory and Practice in the Light of Islamic International Law (Siyar) according to Orthodox Schools is a study that seeks to explain Islamic international legal theory regarding treaties with non-Muslims, The treaties selected in this book cover the full spectrum of what Muslims and non-Muslims could do to develop and to protect the interest of their communities. With a focused subject and approach, Professor Labeeb Ahmed Bsoul discusses the importance of these treaties and their continually changing interpretations. The book aims to shed light on a relatively untouched branch of Islamic law, while simultaneously elucidating the social ramifications of legal theory and practice.